Bibliometric Analysis of Scientific Production on Agricultural Cooperatives in Spanish-speaking Countries. - Camacho-Bercherlt, Mirna; Rojas Herrera, Juan José; Santillán Fernández, Alberto (Cooperativismo & Desarrollo, 2023)
Agricultural cooperatives are social enterprises dedicated to the production, transformation and marketing of agricultural, livestock and forestry products. Its business-associative model is little known due, among other causes, to its scarce diffusion in printed media of a scientific nature. For this reason, the objective of this research was to analyze the spatio-temporal evolution of scientific production on agricultural cooperatives in Spanish-speaking countries, through a bibliometric analysis that would allow identifying the main countries, topics and scope of publications. We collected 164 scientific articles published between 2001 and 2021, in which the spatio-temporal evolution of the research showed a linear growth (R2=0.47, P<0.001), concentrated in Cuba and Spain, countries in which the three journals with the highest number of published articles and with the greatest impact are located, measured by the number of bibliographic citations. Such journals are: CIRIEC-España. Revista de economía pública, social y cooperativa; COODES. Cooperativismo y Desarrollo y REVESCO. Revista de Estudios Cooperativos. The most relevant topics were: organization, cooperation and legislation. However, there is little interaction within the network of authors, which responds to the fact that the study of agricultural cooperatives represents an emerging research topic, with still limited breadth and depth.